Pharmacological Activity and Mechanisms of Action of Terpenoids from Laurus nobilis L. - Kamdem, Boniface P.; Le Doux Kamto, Eutrophe; Soh, Désiré; Pegnyemb, Dieudonné Emmanuel; Zingue, Stéphane; Paumo, Hugues Kamdem; Katata-Seru, Lebogang Maureen; Abou, Aboubakar; Rosinah, Montsho Maiyane; Mbah, James Ajeck; Boyom, Fabrice Fekam (Natural Products Journal, The, 2023)
Native to the Southern Mediterranean region, Laurus nobilis L. (Family Lauraceae) is an evergreen shrub or tree found in warm climate regions with high rainfall. The leaves and essential oil of this plant have been widely used as condiments, spices, and flavoring agents in the culinary and food industries. The whole plant is also used for the traditional treatment of various diseases, including cough, asthma, hemorrhoids, rheumatic pain, diarrhea, intestinal, and cardiac diseases. Previous phytochemical investigation of this plant demonstrated the presence of a variety of secondary metabolites, especially terpenoids. The present study aims to critically analyze comprehensive literature on the pharmacological activity and mechanisms of action of terpenoids from Laurus nobilis L. The available information on the pharmacological activity of terpenoids from L. nobilis L. was obtained from textbooks, theses, as well as published articles through a variety of libraries and electronic databases. The present study demonstrated that L. nobilis is rich in terpenoids, with more than 200 entities identified in reported studies. Terpenoids from L. nobilis have shown a wide range of pharmacological activities, including anti-inflammatory, antidiabetic, antifungal, antibacterial, immunomodulatory, anticonvulsant, antioxidant and cytotoxic activities. The mechanisms of action of most of these terpenoids included the imbalance of the ionic permeability of the cell membrane (anti- inflammatory and antimicrobial activities), modulation of the effects of gamma-aminobutyric acid (GABA) nergic neurotransmission (anticonvulsant activity), and the inhibition of inflammatory responses, prevention of metastasis, and induction of apoptosis (cytotoxic effect), among others. Referring to in vitro studies, terpenoids of L. nobilis L. have shown a variety of biological activities. However, more cytotoxic and in vivo studies and detailed mechanisms of action of the bioactive terpenoids are recommended.
Keywords: toxicity